2021
DOI: 10.1186/s12889-021-11865-8
|View full text |Cite
|
Sign up to set email alerts
|

Supporting participation in paid work of cancer survivors and their partners in the Netherlands: protocol of the SusTained Employability in cancer Patients and their partnerS (STEPS) multi-centre randomized controlled trial and cohort study

Abstract: Background Many cancer survivors experience physical and/or psychosocial problems affecting return to work (RTW) and work retention. Current interventions on RTW lack evidence regarding effectiveness, while interventions for work retention are missing. Partners of cancer survivors may also experience work- and health-related outcomes; yet, these consequences are not well understood. Here, the protocol of the STEPS study is described. The study aims are to: 1) evaluate the (cost-)effectiveness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The current qualitative study is part of the STEPS project (SusTained Employability of cancer Patients and their part-nerS), i.e., a combined randomized controlled trial (RCT) for CSs and cohort study for partners of CSs. Within the STEPS RCT, we will evaluate a behavioral change-based intervention program to support RTW and work retention in CSs [24]. The current study was designed and reported based on the Consolidated Criteria for Reporting Qualitative research (COREQ) checklist [25] (Supplementary File 1).…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The current qualitative study is part of the STEPS project (SusTained Employability of cancer Patients and their part-nerS), i.e., a combined randomized controlled trial (RCT) for CSs and cohort study for partners of CSs. Within the STEPS RCT, we will evaluate a behavioral change-based intervention program to support RTW and work retention in CSs [24]. The current study was designed and reported based on the Consolidated Criteria for Reporting Qualitative research (COREQ) checklist [25] (Supplementary File 1).…”
Section: Designmentioning
confidence: 99%
“…Future research should evaluate the effectiveness of intervention programs that offer stagespecific support for CSs aiming to RTW or retain work. Our research team will do this in an upcoming randomized controlled trial: STEPS [24].…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…Implementing return-to-work programmes can expedite the process of cancer survivors rejoining the workforce, thereby reducing productivity losses. 40 Expanding coverage for supportive care services can address physical and mental health impairments that contribute to disability costs. 41 Investing in research to reduce long-term disability can help lower productivity losses by minimising the long-term effects of cancer and its treatment.…”
Section: Discussionmentioning
confidence: 99%